Pengaruh Distribusi Udara Terhadap Kinerja Tungku Gasifikasi Sekam Padi Tipe Downdraft Continue - Sari, Duwi Prima; , Ir. Subroto, MT; , Wijianto, ST, M.Eng, Sc (2016)
The increasing of population cause the increasing of human needed for energy every year, It will lead to the depletion of existing energy source this energy especially unrenewable energy. So we have to find alternative sources of energy. That can renewable , one of the alternative source of energy that can we found around us is biomass. The example is rice husk, rice husk is used as the producer of alternative energy by using gasification method. Gasification is the transformation procces of thermochemical solid fuel into gas, where is the needed of air are less than the air that used for the process of combustion. This research using a furnace gasification which is the type is downdraft with rice husk as the fuel and use the variation of quantity of a hole in air distributor that entering into a furnace that namely: type 1 (4holes), type 2 (8 holes), and type 3 (12 holes). After that,the researches take the data about temperature, starting time and the effective time to flame. The result of this study show the using of air distributor effected the average of temperature, starting time and the effective time to flame. The use of distributor air type 1 the average of temperature is 547,23°C which is the starting time is 7 minutes and the effective time is 50 minutes. The average time of air distributor type 2 is 524,75°C which is the starting time is 9 minutes and the effective time is 53 minutes. And the average time of air distributor type 3 is 524,05°C which is the starting time is 9,5 minutes and the effective time is 54 minutes. Keywords: Gasification, Air Distributor, Temperature Burning, Rice Husk